Optimalisasi Proses Pengeringan pada Komoditas Pertanian untuk Meningkatkan Kualitas Ekspor - Muhammad Iqbal; Dewi Anggraini (Lembaga Publikasi Ilmiah Nusantara, 2026)
Drying is one of the most important stages in the postharvest handling of agricultural commodities, playing a significant role in determining the final quality of products, particularly those intended for export markets. The optimization of the drying process has become increasingly crucial due to the stringent quality standards imposed by international markets, including moisture content, color, texture, aroma, and nutritional composition. This study aims to analyze and optimize the drying process of various agricultural commodities in order to improve product quality and competitiveness in export markets. The methods employed in this study include experimental approaches and a literature review of various drying techniques, such as conventional drying (sun drying), oven drying, freeze drying, as well as modern technologies including microwave drying and hybrid drying systems. The findings indicate that each drying method possesses its own advantages and limitations depending on the type of commodity being processed. Freeze drying produces the best results in preserving nutritional quality and product structure; however, it involves relatively high operational costs. Meanwhile, hybrid drying technology offers a balance between energy efficiency and the quality of the final product. Factors such as drying temperature, drying time, airflow velocity, and environmental humidity were found to significantly affect the final product quality. Improper control of these parameters may lead to quality deterioration, including color changes, texture hardening, and the loss of volatile compounds essential for flavor characteristics. Optimization of the drying process through appropriate technology and precise parameter control can extend product shelf life, reduce postharvest losses, and increase the economic value of agricultural commodities. Furthermore, the implementation of modern drying systems contributes to energy efficiency and supports the sustainability of agroindustrial activities. Therefore, innovation in drying processes is considered a key factor in enhancing the competitiveness of agricultural products in the global market.